THE TRANSLATION SHIFT OF TRANSLATING ADVERB MANNER WTH SUFFIX â€“LY FROM ENGLISH AS THE SOURCE LANGUAGE INTO INDONESIAN AS THE TARGET LANGUAGE (CASE STUDY OF TRANSLATING NOVELâ€ PIT PENDULUMâ€ BY EDGAR ALAN POE INTO â€œJURANG DAN PENDULUMâ€ BY MAGGIE TIOJAKIN) - Eryon, Eryon; Maretha, Carla; Alrajafi, Gali; Puspita, Rani (Universitas Muhammadiyah Lampung, 2023)
Translating is a process of transferring meaning from the SL forms of words, phrases, clauses and sentences to the TL forms. In translating source language text (English) into target language text (Indonesian) will find some problems because of the different grammatical rules between them. One of the problems occur when translating English adverb of manner with suffix â€“ly into Indonesian is how to change the form of English adverb of manner with suffix -ly into Indonesian adverb of manner since both languages have different grammar system of adverb of manner. This research focused on what kinds of shifts occur when translating adverb of manner sih suffix â€“ly in Poeâ€™s work entitle â€œPit Pendulumâ€ into Indonesian â€œJurang dan Pendulumâ€ by Maggie Tiojakin. The results of analysis were described not in number but in form of narration qualitatively. The results showed that the Unit shift, structure shift, class shift and intra- system shift occurred in translating passive voice of English as SL to Indonesian as TL.